Differences in the effects of orthodontic treatment on airway-craniocervical functional environment in adult and adolescent patients with skeletal class II high-angle: a retrospective pilot study - Yiyang Shen; Xin Li; Xiaoyan Feng; Lan Yu; Luxi Weng; Chenxing Zhang; Yufeng Shang; Jun Lin (BMC, 2023)
Abstract Introduction This retrospective cohort study aimed to compare the change in upper airway and craniocervical posture after orthodontic treatment between adolescent and adult patients with Class II high-angle malocclusion. Methods A total of 12 adolescent (mean ± standard deviation age = 13.0 ± 2.0 years) and 12 adult patients with Class II high-angle malocclusion (mean ± standard deviation age = 23.7 ± 6.4 years) were selected in this study. The lateral cephalograms and cone beam computed tomography images of adolescent and adult patients were taken before and after treatment, which can be employed to evaluate the variables of craniofacial morphology, upper airway, and craniocervical posture through paired t tests, respectively. An independent sample t test was performed to observe the differences between two groups after orthodontic intervention. For adults and adolescents, the correlation between craniofacial morphology, upper airway, and craniocervical posture was determined through Pearson correlation analysis. Results In all subjects, the improvements in vertical and sagittal facial morphology after treatment were observed. Anterior and inferior movements of the hyoid bone, an increase of upper airway dimension, posterior tipping of the head and a reduction of cervical inclination in the lower and middle segments post-treatment were identified in adolescence (P < 0.05). Adults displayed anterior movements of the hyoid bone, whereas no significant difference was observed in upper airway dimension and craniocervical posture (P < 0.05). Notable differences were identified in the change of hyoid position and airway volume between two groups (P > 0.05). Mandibular plane inclination, growth pattern, occlusal plane inclination, and chin position were all significantly correlated with craniocervical posture in adolescent patients. Besides, the mandibular growth pattern and chin position in adult patients were significantly correlated with craniocervical posture (P < 0.05). Conclusions Orthodontic treatment is capable of enhancing the facial profile of patients with skeletal class II high-angle while improving their upper airway morphology and craniocervical posture, where adolescents and adults differ substantially in that the former exhibit a more favorable alteration in the airway-craniocervical functional environment.